Effect of water content on conidia of Trichoderma spp., indole acetic acid content, electrical conductivity, and pH (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Purwanto B, Sumadi, Nuraini A, Setiawati MR. 2022. Effect of water content on conidia of Trichoderma spp., indole acetic acid content, electrical conductivity, and pH. Biodiversitas 23: 2553-2560. Trichoderma sp. is a soil-borne saprophytic fungus that can increase plant resistance to combat drought stress. However, some species are unable to survive in a low water environment. Therefore, this research aimed to determine the effect of water content on different species of Trichoderma with respect to total conidial growth, IAA content, electrical conductivity (EC), and the media’s pH. A factorial Completely Randomized Design (CRD) with 2 factors, namely the water content of the media consisting of 3 levels (5%, 25%, and 50%) and the inoculation of Trichoderma spp. which includes Trichoderma harzianum, Trichoderma asperellum, and Trichoderma viride. Furthermore, an experimental method was adopted by analyzing the total conidial growth, indole acetic acid content (IAA), electrical conductivity (EC), and acidity (pH) of the media. Incubation was carried out for 14 days, data were analyzed using one way ANOVA, and Duncan's Multiple Distance Test was applied to determine the parameters that have a significant effect. The results showed that the total conidia of T. harzianum at the lowest water content (5% of the dry weight of the media) showed an increase from 7th to 14th days after inoculation (DAI), the highest was 23.6%, followed by T. asperellum (12.6%) and T. viride (10.7%). Similarly, the total conidia of Trichoderma spp. positively correlated with the levels of IAA, EC, and pH of the media. This indicates that an increase in total conidia is followed by an increase in the IAA content, EC, and pH. The highest total of T. harzianum conidial growth at the lowest water content indicated that it had better resistance to drought stress than T. asperellum and T. viride.
Keywords: Conidia, indole acetic acid, inoculation, Trichoderma spp., water content